Combined multi-scale characterization of pores in ultra-thick coal seams of Jurassic Xishanyao Formation, Tiaohu-Malang sags, Santanghu Basin - Yue CHEN; Qiqi LEI; Dongmin MA; Xin WANG; Xinggang WANG; Diefang HUANG; Gaoxiang RONG (Shiyou shiyan dizhi)
The ultra-thick coal seams in the middle and lower parts of the Jurassic Xishanyao Formation in the Santanghu Basin are widely distributed. However, research on the pore characteristics of these ultra-thick coal seams is limited. To accurately characterize the porosity features of these coal reservoirs in the Tiaohu-Malang sags of the Santanghu Basin, the study examined the 9-1 and 9-2 coal samples of the Xishanyao Formation. Techniques such as high-pressure mercury intrusion porosimetry, low-temperature liquid nitrogen adsorption, nuclear magnetic resonance (NMR), CT scanning, scanning electron microscopy (SEM), and the pore-crack analysis system (PCAS) were used to investigate pore development characteristics. The results show significant differences in surface morphology between the two coal seam samples. The surface of the 9-1 coal sample contains a large number of mineral crystal particles, with well-developed pores, breccia pores, friction holes, and micro-fractures, displaying a distinct pore-fracture topological structure. The 9-2 coal sample exhibits prominent primary fibrous structures, with smaller and more dispersed fractures. The fractal characteristics of the pore structures also differ significantly between the two coal seams, with the 9-1 coal sample showing stronger heterogeneity. Its liquid nitrogen adsorption curves correspond to type Ⅱ with a H4 hysteresis loop. For the 9-2 coal sample, the fractal dimensions of micropores and small pores are 2.53 and 2.63, respectively, indicating higher complexity and better permeability connectivity. Multifractal characteristics analysis shows that pores of small diameters exhibit a more concentrated distribution and a narrower range, with stronger heterogeneity. The pore distribution of 9-1 coal sample is more concentrated, with a relatively more uniform pore size distribution intervals. Using a combined full-scale characterization method, it is revealed that 9-2 coal sample has a higher total pore volume than 9-1. Macropores have the largest volume proportion, accounting for 47.97% and 44.48%, respectively, followed by mesopores and small pores, and the proportion of micropores is the smallest. Micropores contribute the most to the pore specific surface areas for both seams, which are 62.67% and 58.43%, respectively. For the 9-1 coal sample, the pore volume contribution positively correlates with pore size, while the specific surface area contribution negatively correlates with pore size.